Microbial pattern and antibiotic sensitivity test of hospitalized children - Wiwin, John; Rejeki, IGAA Putri Sri (Folia Medica Indonesiana, 2016)
Infection often occurs in children with malignant hematology and causes morbidity and mortality in the children. Antibiotics given must be based on culture results and antibiotic sensitivity testing. This study was aimed to obtain the microbial pattern and sensitivity test in children hospitalized in the Hemato-Oncology Ward, dr. Soetomo Hospital from September 2012 - February 2013. This was a descriptive study. Data were obtained from the patients' medical records in Dr. Soetomo Hospital. There were 341 culture examinations (blood, urine, rectum swab, faecal, and others) from 88 patients (44 males and 44 females). Most of patients´ age was < 5 years (58%) and suffered from ALL (50%).There were microbial (83 of culture) and yeast (15 of culture) growth out of 98 cultures. Escherichia coli, Burkholderia cefacea, and Klebsiella oxytoca (Gram negative) dan CONS, Stapyloccocus aureus, and Stapylococcus sapropyticus (gram positive) were found in blood culture. S. aureus (gram positive) and E. coli, Klebsiella pneumoniae, and B. cefacea (gram negative) were found in urine culture. Only E. coli was found in rectal swab culture. CONS of gram positive cocci were mostly found in blood culture of children hospitalized in Hemato-Oncology Ward, Dr. Soetomo Hospital. E. coli was the mostly found gram negative rods. Gram positive cocci showed a high resistant to penicillin and co-trimoxazole. E. coli, mostly found in rectal swab and urine, has a high sensitivity to amikacin and meropenem, but highly resistant to ampicillin and ampicillin sulbactam.